2020
DOI: 10.1111/cas.14352
|View full text |Cite
|
Sign up to set email alerts
|

Expression, mutation, and methylation of cereblon‐pathway genes at pre‐ and post‐lenalidomide treatment in multiple myeloma

Abstract: Cereblon (CRBN) is a target for immunomodulatory drugs. This study investigated the prognostic value of the expression of CRBN-pathway genes on the clinical relevance of lenalidomide (Len) treatment and evaluated the levels of CRBN-binding proteins and mutations in these genes after Len treatment. Forty-eight primary multiple myeloma cells were collected prior to treatment with Len and dexamethasone (Ld) and 25 paired samples were obtained post-Ld therapy. These tumor cells were used to determine the expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…In recent years, The dysregulation and/or prognostic roles of KPNA2 were reported in many tumors including esophageal squamous cell carcinoma (Song et al, 2019), breast cancer (Groheux et al, 2018;Wang et al, 2019a), myeloma (Kriegsmann et al, 2019;Tachita et al, 2020), clear cell renal cell carcinoma (Müller et al, 2019), oral cancer (Wang et al, 2018), bladder cancer (Jeong et al, 2017), and colorectal cancer (Ostasiewicz et al, 2016;Jeong et al, 2017). The immune-related roles of KPNA2 were also shown in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, The dysregulation and/or prognostic roles of KPNA2 were reported in many tumors including esophageal squamous cell carcinoma (Song et al, 2019), breast cancer (Groheux et al, 2018;Wang et al, 2019a), myeloma (Kriegsmann et al, 2019;Tachita et al, 2020), clear cell renal cell carcinoma (Müller et al, 2019), oral cancer (Wang et al, 2018), bladder cancer (Jeong et al, 2017), and colorectal cancer (Ostasiewicz et al, 2016;Jeong et al, 2017). The immune-related roles of KPNA2 were also shown in tumors.…”
Section: Introductionmentioning
confidence: 99%
“…DNA samples from the bone marrow of IMiD and PI doublerefractory MM patients have been examined using nextgeneration sequencing, and CRBN pathway-related mutations were identified in 32.5% of the patients [18]. Other reports have shown that most patients treated with lenalidomide have downregulated CRBN and upregulated IKZF1 gene expression [19]. CRBN mutations are also associated with pomalidomide resistance in MM [20].…”
Section: Introductionmentioning
confidence: 99%
“…Immunomodulatory drugs such as thalidomide, lenalidomide, and pomalidomide modulate the inflammatory environment of the bone marrow, causing MM cell death by inhibiting angiogenesis and antiproliferative properties [ 22 ]. Cereblon (CRBN) is a target for immunomodulatory drugs [ 23 ], and lenalidomide-bound cereblon acquires the ability to target two specific B cell transcription factors, Ikaros family zinc finger proteins 1 and 3 (IKZF1 and IKZF3), for proteasomal degradation [ 24 ]. Another promising treatment for MM is anti-B cell maturation antigen (BCMA) chimeric antigen receptor (CAR) T cell therapy.…”
Section: Multiple Myeloma Is the Second Most Common Hematological Malignancy: Current Treatment Strategiesmentioning
confidence: 99%